CRIMINAL LIABILITY FOR JUSTICE COLLABORATORS INVOLVED IN CORRUPTION CRIMES IN INDONESIA - Khoirunnisa Khoirunnisa; Didi Jubaidi (Kanun Jurnal Ilmu Hukum, 2023)
Corruption has become increasingly pervasive in society, necessitating solutions to combat it. One such solution involves the collaboration of witnesses, known as Justice Collaborators. This study aims to determine the criminal liability of Justice Collaborators involved in corruption crimes. This study adopts a normative juridical method, which involves examining library materials comprising primary, secondary, and tertiary legal sources. The data for this study is derived from literature, existing research, as well as relevant laws and regulations. The findings indicate that Justice Collaborators can be held criminally liable by applying the concept of strict liability, as they fulfill the elements of a criminal offense, namely actus reus and mens rea. However, it is important to note that even though a Justice Collaborator may be convicted, they are still entitled to their rights and may be granted leniency.